A transmural gradient of myocardial remodeling in early‐stage heart failure with preserved ejection fraction in the pig. Issue 3 (21st November 2019) - Mühlfeld, Christian; Rajces, Alexandra; Manninger, Martin; Alogna, Alessio; Wierich, Marie‐Christin; Scherr, Daniel; Post, Heiner; Schipke, Julia
Abstract: Heart failure with preserved ejection fraction (HFpEF) is characterized by diastolic dysfunction. This study aimed to analyze whether early HFpEF is already associated with ultrastructural alterations and whether they differ quantitatively among the layers of the left ventricular wall. HFpEF was induced in pigs by deoxy‐corticosterone acetate (DOCA) treatment along with a high‐salt/high lipid diet over 3 months and compared with weight‐matched normal pigs ( n = 5 each). Samples of the left ventricle were taken and processed for light and electron microscopy. Interstitial fibrosis, subcellular composition of cardiomyocytes and mean cardiomyocyte diameter were evaluated by stereology in subendocardial, midmyocardial and subepicardial regions. DOCA enhanced the mean cardiomyocyte diameter in all locations of the ventricle wall to the same degree. The subcellular composition did not differ between the locations and was not altered by DOCA. The volume fraction of interstitium was smaller in the subendocardium of DOCA group than of control group. Within the interstitium, the volume fraction of collagen fibrils (between cardiomyocytes) was increased in the subendocardial and midmyocardial wall layers of the DOCA group but not in the subepicardial layer. Although the capillary length density and average supply area were not altered in response to DOCA in any of the wall layers, the volume fraction of blood vessels related to the interstitial space was enhanced in the subendocardium of the DOCA group but not in the other wall layers. In conclusion, cardiomyocyte changes due to DOCA were similar in subepicardial, midmyocardial and subendocardial regions but DOCA‐induced changes in the interstitium appeared to be more pronounced in the subendocardial ventricular wall layers. This suggests a pivotal role of the subendocardial interstitium in the pathogenesis of HFpEF. Abstract : Heart failure with preserved ejection fraction is a relatively new entity in cardiac research. Here, we used a large animal model to analyze differential morphological changes across the left ventricular wall. Our data support the concept that the subendocardial interstitium plays a pivotal role in the pathophysiology of heart failure with preserved ejection fraction.